Factors Influencing E-learning Practices - Rajagopal, Kavita Nair (2010)
E-learning practice is committed to develop an organization and to bring about a revolution to the traditional learning practice. E-learning practices is derived and developed with supporting factors to achieve the needs and wants of the organization. The factors and characteristic of e-learning provide the concatenation of technology with learning objective. The factors and characteristics forms the backbone of e-learning, this study incorporates factors like employee skills and attitude, infrastructure, trainers expertise and budget. The study is carried out to describe the relationship and the perception of e-learning and its factors. Toda’s business environment is pushed to a state where e-strategy becomes the prime development objective of the organization. E-learning complements the e-strategy with its dynamicity but this provides an insignificant approach towards incorporating e-learning practices. Without proper standards and understanding of the factors it creates a challenge to successfully practice e-learning. A total of 124 respondents from two companies were used with a survey method of questionnaire to gather the necessary data pertaining to e-learning practices. The gathered data was analyzed using a series of analysis consisting of repeated measure, Pearson (r) correlation and multivariate regression. The research identified that factors like employee skills and attitude and infrastructure proved to be a vital component to e-learning practices. On the other hand, budget and trainers expertise did not contribute as much towards e-learning practices as compared to the other factors. Although all the factors influencing e-learning practices used in this study has a significant relationship, the impact level varies from one another. As a result, organization incorporating e-learning practices is required to vitalize the factors based on the needs and wants.